Women’s Humility and Men’s Lack of Hubris: Gender Biases in Self-Estimated Spatial Intelligence. - Hofer, Gabriela; Hünninghaus, Marla; Platzer, Jana; Grinschgl, Sandra; Neubauer, Aljoscha (Sex Roles, 2025)
Women tend to view themselves as less capable than men. Some have interpreted this as female underestimation and male overestimation, a phenomenon called hubris-humility effect. While such an effect could have important practical implications (e.g., on career choices), only few studies compared women's and men's self-estimates to their measured abilities. We investigated the hubris-humility effect in spatial intelligence, a domain in which many studies reported women’s and men’s abilities to differ substantially. Participants (n = 208; 103 women and 105 men; aged 18–37) completed self-estimate and performance measures of spatial intelligence and additional questionnaires on personality and interests. Surprisingly, women and men performed similarly well in the spatial tests. Still, women, on average, provided more negative self-estimates of their overall spatial intelligence and concrete test performance than men. This constituted female humility but not male hubris: Women underestimated themselves, but men did not overestimate themselves. To contextualize the effect, we tested associations between misestimation and specific personality traits (narcissism and honesty-humility). Especially people higher in grandiose narcissism provided overly positive self-estimates. However, even when we accounted for individual differences in grandiose narcissism, women still underestimated themselves more than men. We further investigated interests in science, technology, engineering, and mathematics (STEM) careers. Women reported lower STEM interests than men—interests that, in turn, showed stronger associations to self-estimated than measured spatial intelligence. Our findings suggest that improving women’s self-views in the spatial domain might contribute towards greater gender equality in STEM.